Ethics in qualitative research : controversies and contexts - Hammersley, Martyn. (SAGE Publications, 2012)
"All researchers need to think about research ethics, and for a variety of reasons it is an increasingly important part of research methods training. Ethics in Qualitative Research explores this field and presents a distinctive perspective; one that is at odds with the assumptions underpinning ethical regulation, but also with the views of many qualitative researchers today. Martyn Hammersley and Anna Traianou emphasize the difficult and controversial character of ethical issues, and examine the philosophical assumptions involved, the social contexts in which key ethical principles arise, and their implications for research practice. The authors argue that the starting point for any discussion of research ethics must be the values intrinsic to research, above all the commitment to knowledge-production. However, the pursuit of inquiry is rightly constrained by external values, and the book focuses on three of these: minimizing harm, respecting autonomy, and protecting privacy. These values are shown to be far from unequivocal in character, often in conflict with one another, or with the commitments of research, and always subject to situational interpretation and practical judgment. It is argued that in the present challenging times it is essential that qualitative researchers think clearly about, and stand up for, their principles"--Publisher's website.